Pandemic against the clock: A study on the shift in time perception in academia, institutions, and data (2023)
COLEV is an interdisciplinary group at Universidad de los Andes dedicated to producing and communicating pertinent evidence with a gender perspective. Our aim is to foster dialogue between academia and public health decision makers, providing informed responses to the challenges posed by COVID-19 in Colombia. This summary presents key findings from our team of COLEV researchers, who specialize in qualitative methodologies. They focused on the topic of 'Decisions and Data,' to identify the perceived preferences and needs of decision makers within the country's health ecosystem. Spanish versión: http://hdl.handle.net/1992/66225